Combination of Apolipoprotein A1‐Modi Liposome–Doxorubicin with Autophagy Inhibitors Overcame Drug Resistance In Vitro. Issue 12 (29th October 2014) - Wang, Baolong; Feng, Duo; Han, Lei; Fan, Jiajun; Zhang, Xiaozhe; Wang, Xin; Ye, Li; Shi, Xunlong; Feng, Meiqing
<x xml:space="preserve">Abstract</x> Multidrug resistance (MDR) represents the major drawback in chemotherapy. Liposome‐based approaches could reverse MDR to some extent through circumventing the active efflux effect of P‐glycoprotein. However, the reverse power of liposome is very limited because the nontargeting liposome is inefficient to deliver drugs to tumor actively. Besides, autophagy could reinforce the resistance of tumor cells to the cytotoxicity of intracellular drugs. Here, liposomal doxorubicin (Lipodox) that was conjugated with apolipoprotein A1–apo‐Lipodox, was employed in tumor targeting delivery of doxorubicin. In the experiments, apo‐Lipodox could enter cells effectively and reverse MDR more efficiently than their nontargeting counterpart. Autophagy occurred in this process and contributed to the survival of tumor cells. Combination use of autophagy inhibitors could enhance the cytotoxicity of apo‐Lipodox and reverse drug resistance to a higher degree. We propose that this strategy holds promise to overcome MDR in human cancer. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3994–4004, 2014